2021
DOI: 10.1007/s12237-021-00973-8
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic, Temporal, and Spatial Variations in Zooplankton Fatty Acid Composition in Puget Sound, WA, USA

Abstract: Fatty acid (FA) content and composition of zooplankton in Puget Sound, Washington (USA) was studied to investigate the nutritional quality of diverse zooplankton prey for juvenile salmon (Oncorhynchus spp.) in terms of their essential fatty acid (EFA) content. The study focus was on eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and arachidonic acid (ARA) as these are key FA needed to maintain growth and development of juvenile fish. The different zooplankton taxa varied in their FA composition. Much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Large calanoid copepods, such as Neocalanus plumchrus and Calanus marshallae, and amphipods have higher DHA+EPA concentrations than other species. Our data showed that the JS zooplankton community was dominated by small copepod species, which tend to have low FA content (Hiltunen et al, 2021).…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Large calanoid copepods, such as Neocalanus plumchrus and Calanus marshallae, and amphipods have higher DHA+EPA concentrations than other species. Our data showed that the JS zooplankton community was dominated by small copepod species, which tend to have low FA content (Hiltunen et al, 2021).…”
Section: Discussionmentioning
confidence: 63%
“…Large calanoid copepods, such as Neocalanus plumchrus and Calanus marshallae , and amphipods have higher DHA+EPA concentrations than other species. Our data showed that the JS zooplankton community was dominated by small copepod species, which tend to have low FA content (Hiltunen et al, 2021). Both the NSoG and QCS had a high abundance of larger copepods, euphausiids, and amphipods, with the latter two groups both having relatively large size (> 10 mm) and high DHA and EPA content (Hiltunen et al, 2021), i.e., prey was more nutritious in the NSoG and QCS than JS.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations